Meditations on First Philosophy - René Descartes 1596-1650; Laurence J. Lafleur (tr.) (USA Bobbs-Merrill, 1960)
The translation of the Meditations is taken from three sources: the second Latin edition of 1642, which was the first one printed from Descartes' own manuscript and under his own supervision, the first French translation of 1646 by Duc de Luynes, but read and approved by Descartes, and the second French translation by Clerselier. An attempt has been made in this translation to integrate these three versions into one complete and accurate edition by the use of brackets and parentheses. The reader may, by omitting the parentheses and brackets, have a translation which contains all ideas in the three versions. By omitting bracketed material, he will have a translation essentially that of the original Latin, and by omitting material in parentheses, that of the First French edition
Letter to the faculty of Theology of Paris -- Preface -- Synopsis -- Concerning things that can be doubted -- Of the nature of the human mind, and that it is more easily known than the body -- Of God : that he exists -- Of the true and the false -- Of the essence of material things, and, once more, of God: that he exists -- Of the existence of corporeal things and of the real distinction between the mind and the body [of man]
Keywords: Philosophy and Psychology; First philosophy -- General; God -- Proof, Ontological -- Early works to 1800; Methodology -- Early works to 1800; Knowledge, Theory of -- Early works to 1800